New water management fellowships for women - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Fellowships for the MSc course Irrigation and Water Management at Wageningen Agricultural University in the Netherlands will be awarded to female professionals in water management. The English-language course consists of 11 months course work, 3...